Reducing PAPR of OFDM Using PTS Techniques for Different Number of Sub-blocks - Abdullah, Md. Ibrahim; Kundu, Sajib Kumar; Hossain, Md. Shamim; Mahmud, Md. Zulfikar (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Orthogonal Frequency Division Multiplexing (OFDM) technology promises to be a key technique for achieving the high data capacity and spectral efficiency requirements for wireless communication system of the near future. Peak to average power ratio (PAPR) is a major drawback of multicarrier transmission system which leads to reduce the efficiency of Radio Frequency (RF) amplifiers and increase the complexity in the analog to digital and digital to analog conversion. In this paper, we present PAPR reduction on Partial Transmit Sequences (PTS) method using different number of sub-blocks. Simulation result shows that the PAPR reduces when the numbers of subblocks are increases.